DETEKSI MIKROSKOPIS OOKISTA TOXOPLASMA GONDII PADA FESES KUCING MELALUI FLOTASI SENTRIFUGASI DI MALAKA SARI, JAKARTA TIMUR - Nurul Azmah Nikmatullah; Muhammad Nur Fai; Siti Nuril Aprilianti; Oktadio erikardo; Euis Purbasari; Adia Putra Wirman; Rahmat Subakry (Kieraha Medical Journal, 2026)
Toxoplasma gondii is an obligate intracellular protozoan parasite with zoonotic potential. It is transmitted through the feces of domestic cats (Felis catus) containing oocysts. Data on active oocyst shedding by cats in East Jakarta, particularly in Malaka Sari Village, remain limited. This study aimed to identify the presence of T. gondii oocysts in cat fecal samples using the centrifugal flotation method. This was a descriptive cross-sectional study conducted on 70 cat fecal samples collected from Malaka Sari Village, Duren Sawit District, East Jakarta. Each sample was processed by centrifugal flotation using a saturated salt solution of high specific gravity to concentrate parasitic elements, after which the surface film was examined under a light microscope at 400× magnification. Oocysts were identified based on their morphological characteristics, and the data were analyzed descriptively as frequencies and percentages. Of the 70 fecal samples examined, 2 (2.86%) were positive for oocysts morphologically consistent with T. gondii, whereas 68 (97.14%) were negative. The observed oocysts were oval to subspherical, with thin walls and granular internal structures. Because light microscopy cannot reliably distinguish T. gondii oocysts from those of Hammondia hammondi and Cystoisospora spp., these findings should be interpreted as morphologically consistent rather than confirmed; therefore, molecular confirmation by PCR is recommended. The detection of these oocysts indicates ongoing environmental contamination and a potential zoonotic risk, and underscores the need for continued surveillance, improved sanitation, and integrated control based on the One Health approach.